Combining quantitative and qualitative research methods to foresee the changes in the Finnish agri-food sector - Huan-Niemi, Ellen; Rikkonen, Pasi; Niemi, Jyrki; Wuori, Olli; Niemi, Janne (Elsevier Science, 2016)
This paper focuses on the benefit of using two different research methods interactively, namely the Global Trade Analysis Project (GTAP) model and Delphi method. This is relevant in the current discussion in futures studies to integrate quantitative research methods with qualitative research methods. This undertaking is intended to improve and increase the depth of the knowledge base needed in decision making. We present examples on how this can be achieved and evaluate the strength and weaknesses of each method. We also discuss the benefits of combining both methods by confronting the weaknesses of the methods with the strengths of each method.
Keywords: quantitative method; qualitative method; GTAP model; combining; delfoimenetelmä